The Limits of Scientific Gaze: Exploring the Contradictions of Contagion, 2011 - Korstanje, Maximiliano E.; Skoll, Geoffrey (International Journal of Humanities and Social Science Research, 2015)
This essay explores the synopsis of the film Contagion (2011) that narrates the ethical dilemma of sacrifice in a post-disaster context. At first glance, it seems to emulate the situation during Swine flu outbreaks, radicalizing the political discourse in two directions. On one hand, China, a new emerging but undemocratic superpower, is portrayed as dangerous, disordered, and the Chinese as lazy. In the movie, the United States government intervenes to maintain the security of world health. The US intervention entails restricting the rights of democratic life such as mobility, trade, connectivity, and the distribution of food. The implication is that mobility and tourism facilitate virus outbreaks. This movie presents an ethnocentric discourse because it assumes that only mobility in the First world is safe. Global connections which enable the introduction of Third World from presumed uncivilized cultures lead to the possibility of apocalyptic pandemics.